Pengembangan PENGEMBANGAN MICROSITE INTERAKTIF UNTUK MATERI PKn ” PATUH ATURAN” DI KELAS II SEKOLAH DASAR: Integrasi Teknologi Digital dalam Pembelajaran Pendidikan Kewarganegaraan untuk Siswa Sekolah Dasar - sari, dita; Oktaviani Adhi Sucitaningsih; Riska Pristiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Civic Education has an important role in shaping students' character and responsibility from an early age. However, facts in the field show that Civics learning in elementary schools is still centered on the teacher and does not involve active student interaction, exacerbated by the limitations of interactive learning media. As a result, students become less enthusiastic and unmotivated in the learning process. Along with technological developments, teachers are required to be more innovative in using digital media to create fun and effective learning. This study aims to develop interactive learning media based on microsite as an innovative solution in delivering material “Obey the Rules” for grade II elementary school students. The method used is research and development (R&D) with the Richey & Klein development model consisting of four main stages: analysis, design, development, and evaluation. The subjects of this study were a class teacher and 25 grade II students at Negeri Ngajum Elementary School, Malang Regency. The development process includes needs analysis through observation, content and media design, development of interactive appearance and features, and product evaluation by material experts and media experts. The validation instrument was used to assess the feasibility of the media from the content and technical aspects. The validation results showed that the microsite learning media was rated “very feasible” by both validators with an assessment score in the high category. Thus, this microsite media is proven to be valid and potential as an interactive tool to improve the quality of Civics learning in elementary schools.